2016
DOI: 10.1186/s12888-016-1009-0
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of adverse drug events and medication errors among psychiatric inpatients in Japan: the JADE study

Abstract: BackgroundKnowledge of the epidemiology of adverse drug events (ADEs) and medication errors in psychiatric inpatients is limited outside Western countries. The nature of ADEs and medication errors are important for improving the quality of care worldwide; therefore, we conducted the Japan Adverse Drug Events Study, a series of cohort studies at several settings in Japan.MethodsThis report included 448 inpatients with 22,733 patient-days in a psychiatric hospital and psychiatric units at a tertiary care teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…This result can be compared with the American Psychiatric Association's action for patient safety [27], which estimated that half of drugrelated AEs could have been prevented. Non-psychiatric drugs are associated with preventable AEs more often than psychiatric drugs [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…This result can be compared with the American Psychiatric Association's action for patient safety [27], which estimated that half of drugrelated AEs could have been prevented. Non-psychiatric drugs are associated with preventable AEs more often than psychiatric drugs [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the incidence of ADEs and medication errors in psychiatric inpatients in non-Western countries are scarce. An epidemiological study in psychiatric healthcare centers in Japan reported an incidence of 17.5 medical errors per 1000 patient-days (Ayani et al, 2016), but the specific information regarding the occurrence of DDIs was not made available. Similar studies in countries of the Middle East were not undertaken thus far and the current work begins to address this unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…Mood stabilizers play a pivotal role in the long-term treatment of patients with bipolar disorder. While it is known that mood stabilizers effectively treat symptoms of bipolar disorder, the potential for adverse drug events (ADEs) is of concern (Rothschild et al 2007 ; Ayani et al 2016 ; Mann et al 2008 ). Some ADEs are preventable, and steps to minimize errors are needed to improve patient safety (Leendertse et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%